MDCK cells express serotonin-regulable 11β-hydroxysteroid dehydrogenase type 2 - Zallocchi, M.L. (2006)
Prior to this work, we found that adrenal as well as extra-adrenal factors activate the response of renal l 11β-hydroxysteroid dehydrogenase 2 to stressful situations. These results -showing ways through which the organism hinders the pathological occupation of mineralocorticoid receptors by glucocorticoids leading to sodium retention and hypertension- prompted the present study on the nature of the above-mentioned extra-adrenal factors. Serotonin was chosen because of its properties as a widely distributed neurohormone, known to interact with glucocorticoids at many sites, also exhibiting increased levels and effects under stressful situations. We studied serotonin effects on 11β-hydroxysteroid dehydrogenase 2 activity in a cell line derived from distal nephron polarized-epithelium, employing 3H-corticosterone as substrate. The end-product, 3H-11- dehydrocorticosterone was separated from the substrate by HPLC and quantified. Serotonin stimulated 11β-hydroxysteroid dehydrogenase 2 activity only at 2nM and 25pM, the magnitude of the response depending also on substrate concentration. The stimulation was blocked by the specific inhibitors methiothepin and ketanserin. We postulate that the organism partially prevents renal mineralocorticoid receptor occupancy by glucocorticoids, circulating at enhanced levels under stressful situations, through serotonin-mediated catabolic regulation of the 11β-hydroxysteroid dehydrogenase 2 activity. Given many, mostly positive, interactions between both hormones, this might eventually pave the way to studies on a new regulatory axis.